2022
DOI: 10.1021/acs.jmedchem.2c00670
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Proline-Based p300/CBP Inhibitors Using DNA-Encoded Library Technology in Combination with High-Throughput Screening

Abstract: E1A binding protein (p300) and CREB binding protein (CBP) are two highly homologous and multidomain histone acetyltransferases. These two proteins are involved in many cellular processes by acting as coactivators of a large number of transcription factors. Dysregulation of p300/CBP has been found in a variety of cancers and other diseases, and inhibition has been shown to decrease Myc expression. Herein, we report the identification of a series of highly potent, proline-based small-molecule p300/CBP histone ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The final compound 6-((trans-4-(5-acetyl-3- (34). The final compound 34 was prepared from methyl trans-4-hydroxycyclohexane-1-carboxylate (59c) using the similar procedure for synthesis of final compound (35) 64 (33 mg, 1.0 equiv) was dissolved in anhydrous DCM (5 mL), and the solution was degassed and charged 3 times with N 2 . DIBAL (25% in toluene, 153 μL, 4.0 equiv) was added dropwise at −78 °C over 1 h, and the reaction mixture was stirred at −78 °C for an additional 2 h. Then the reaction was quenched with aqueous potassium sodium tartrate and warmed to rt.…”
Section: Synthesis Of the Final Compound 6-(6-(4-(5-acetyl-3-(7-(difl...mentioning
confidence: 99%
See 3 more Smart Citations
“…The final compound 6-((trans-4-(5-acetyl-3- (34). The final compound 34 was prepared from methyl trans-4-hydroxycyclohexane-1-carboxylate (59c) using the similar procedure for synthesis of final compound (35) 64 (33 mg, 1.0 equiv) was dissolved in anhydrous DCM (5 mL), and the solution was degassed and charged 3 times with N 2 . DIBAL (25% in toluene, 153 μL, 4.0 equiv) was added dropwise at −78 °C over 1 h, and the reaction mixture was stirred at −78 °C for an additional 2 h. Then the reaction was quenched with aqueous potassium sodium tartrate and warmed to rt.…”
Section: Synthesis Of the Final Compound 6-(6-(4-(5-acetyl-3-(7-(difl...mentioning
confidence: 99%
“…Compound 34 was obtained as a light yellow solid; UPLC-MS: 1. 33 (35) 64 (33 mg, 1.0 equiv) was dissolved in anhydrous DCM (5 mL), and the solution was degassed and charged 3 times with N 2 . DIBAL (25% in toluene, 153 μL, 4.0 equiv) was added dropwise at −78 °C over 1 h, and the reaction mixture was stirred at −78 °C for an additional 2 h. Then the reaction was quenched with aqueous potassium sodium tartrate and warmed to rt.…”
Section: Synthesis Of the Final Compound 6-(2-(4-(5-acetyl-3-(7-(difl...mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple domains have been characterized in p300/CBP protein. ,, Among them, the histone acetyltransferase (HAT) domain catalyzes the acetylation of lysine residues on histone tails, directly altering chromatin architecture and thereby promoting transcriptional activation of target genes. , The acetyl-lysine (Kac) binding function of bromodomain (BD) mediates the recognition and engagement of p300/CBP to the enhancer and promotor of target genes and is essential for HAT activity. , Due to the critical role of p300/CBP HAT domain and bromodomain in oncogenic transcription, enormous medicinal efforts have been made, , and our group also previously reported several series of potent and selective small-molecule inhibitors targeting these domains. Although a few potent and drug-like HAT inhibitors have been reported, none of them have yet entered clinical development. Notably, a recent study revealed that the elevated intracellular AcCoA, the substrate of the HAT domain, confers acquired resistance to current HAT inhibitors in cancer cells .…”
Section: Introductionmentioning
confidence: 99%